Problems Faced by Children with Cancer in Sarawak, Malaysia - Kaur, Parveen; Mazhar Farid Chishti, Arif Jawaid, Khalil ur Rehman Muhammad Gul Sher, Abdul Khaliq Alvi, (Opción, 2019)
This study aims to examine the demographic profile of children with cancer, mode of transportation to the hospital, financial aid, knowledge and sources of knowledge of parents and coping strategies by the parents of children with cancer via comparative qualitative research methods. It is found that social support is the fundamental base that every family should have. In conclusion, parents must know how to handle difficult situations wisely because they are the main pillars of a family and they need to be positive in order to help their ill child.